DAMPAK KINERJA KARYAWAN SETELAH DIBERI PELATIHAN PADA PERUSAHAAN SOCIAL MEDIA PLATFORM DI JAKARTA - Andreas Pieter; Catarina Cori (Fakultas Ilmu Administrasi Universitas Krisnadwipayana Jakarta, 2021)
This study is intended to determine the description of the training, the supporting and inhibiting factors for the implementation of the training, as well as the performance of employees after being given training. The research was conducted at PT. Sotta Teknologi Indonesia with qualitative research methods. The results of the study show that the training method is carried out by means of employees working directly in their fields while at the same time receiving training in the form of practice while working. The training provided is basic in nature and advanced in nature as measured by training materials, training methods, attitudes and skills, length of time for training and training facilities. Supporting factors are bounding in a strong team, facilities and tools used during running events and adequate human resources (HR) as mentors, while inhibiting factors include employees not being confident when they are expected to have more expectations, when the event runs for a long duration. which is short so that sometimes it is not enough to apply the training method, at least there are people who are used as mentors here and when the project is empty and there are no events that can train employees. Employee performance after being given training for the last 5 months is getting better and smoother in every job. Employees are no longer given direction although there are still some employees who have not seen a clear improvement in this method of job rotation because it is still rarely done.